Information system outsourcing: motivations and the implementation strategy in a Malaysian bank - Suhaimi, Mohd Adam; Hussin, Husnayati; Mustaffa, Muzzafar (Emerald Group Publishing Limited, 2007)
Purpose – This paper aims to aid in understanding the motivations for information system (IS) outsourcing decision and its initial implementation at one of the top commercial banks in Malaysia. The scope of the study includes the motivating factors, the implementation strategy and managing the change process. Design/methodology/approach – The study adopts a case study approach where 40 interviews were conducted among the staff, covering the management as well as non-management group. Findings – The findings of the study indicate that the motivating factors are the focus on core competencies, turning non-profit activities into profit-generating activities, and cost reduction. The implementation strategy involves the setting up of a two-tier relationship between the bank and the service provider. The challenges involved in the transition phase include managing the partnership and handling the staff transition and morale. Research limitations/implications – To some extent, there may be some subjectivity involved in interpreting the results of analysis, as with any other studies that adopt a case study approach. Practical implications – Amidst the complexity involved in any IS outsourcing endeavour, the management of a bank may learn some lessons from the experience reported in this study. At the initial stage, the bank should be concerned with the approach in establishing the partnerships and staff matters should not be undermined. Originality/value – The study provides a real life example of IS outsourcing implementation in the banking sector of a developing country.